2004
DOI: 10.1111/j.1471-4159.2004.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin‐directed inhibitors of γ‐secretase trigger caspase 3 activation in presenilin‐expressing and presenilin‐deficient cells

Abstract: The amyloid b peptide (Ab) is generated by subsequent cleavages by b-and c-secretases. Therefore, these two enzymes are putative therapeutic targets to prevent Ab production, and hopefully to slow down or even stop the Alzheimer's disease (AD) neurodegenerative process. Several studies have revealed that c-secretase hydrolyses other important substrates besides b-amyloid precursor protein (bAPP) thus adding another level of complexity to designing fully AD-specific interfering drugs. Here we demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…These findings suggest that KSHV infection in KS may be important to constitutive Notch activation in KS tumor cells, and studies are in progress to determine if KSHV infection alters Notch expression and/or activation. Our results showing GSI induces apoptosis in KS cells are consistent with a recent report demonstrating that GSIs indirectly activate caspase-3 in murine cells, and a study showing induction of apoptosis in melanoma cells (Alves et al, 2004;Qin et al, 2004). In that study, the investigators (including BJN and LM) found that malignant melanoma cells, which are notoriously resistant to apoptosis, can be effectively killed by GSI through the mitochondrial-based apoptotic pathway.…”
Section: Discussionsupporting
confidence: 82%
“…These findings suggest that KSHV infection in KS may be important to constitutive Notch activation in KS tumor cells, and studies are in progress to determine if KSHV infection alters Notch expression and/or activation. Our results showing GSI induces apoptosis in KS cells are consistent with a recent report demonstrating that GSIs indirectly activate caspase-3 in murine cells, and a study showing induction of apoptosis in melanoma cells (Alves et al, 2004;Qin et al, 2004). In that study, the investigators (including BJN and LM) found that malignant melanoma cells, which are notoriously resistant to apoptosis, can be effectively killed by GSI through the mitochondrial-based apoptotic pathway.…”
Section: Discussionsupporting
confidence: 82%
“…Because g-secretase is required for proteolytic cleavage of Notch receptors, we hypothesized that these inhibitors also show activity against Notch signaling in lung cancer cells. Inhibitors of g-secretase have been shown by some investigators to reduce angiogenesis and induce apoptosis in other systems, further supporting the hypothesis that these compounds may have utility in the treatment of patients with cancer (17)(18)(19)21). Although Notch signaling has been shown to be important in lung cancer biology, to date, the effects of these inhibitors on lung cancer is largely unknown.…”
Section: Discussionmentioning
confidence: 91%
“…Not surprisingly, because g-secretase protein complex is also necessary for Notch processing, g-secretase inhibitors developed as potential treatment for Alzheimer's disease also block Notch activation and induce apoptosis in multiple cancer cell lines (17)(18)(19)(20). In vivo, these compounds inhibit angiogenesis and tumor growth (21).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pro-apoptotic signal by the secretase inhibitor may be more potent in the modulation of neutrophil apoptosis than the anti-apoptotic signal of Aβ. It was found that the direct addition of Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) to the cultured neutrophils failed to exert an anti-apoptotic effect on the neutrophils even though it has been shown that Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in fibrillary state induces O 2 − and Aβ(1-42) production [3]. Therefore, it is possible that Aβ(1-40) can inhibit neutrophil apoptosis in the monomer state.…”
Section: Discussionmentioning
confidence: 98%
“…Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), Aβ(1-40), Aβ(1-42), Aβ , and Aβ(40-1) were purchased from Bachem AG. The zVADfmk, zDEVD-fmk, zIETD-fmk, β-secretase inhibitor II (z-VLL-CHO), β-secretase inhibitor III (H-EVNstatineVAEF-NH 2 ), γ-secretase inhibitor I ( Z -Leu-Leu-NorLeue-CHO), γ-secretase inhibitor II (Boc-VI-NHCH(CH 3 )-COCF 2 -CO-NHVI-OCH 3 ), γ-secretase inhibitor XI (7-amino-4-chlroro-3-methylisocoumarin), phosphoinositide 3-kinase (PI 3-K) inhibitor (LY294002), phospholipase C (PLC) inhibitor (U73122), phospholipase A 2 (PLA 2 ) inhibitor (MAFP), and protein kinase C (PKC) inhibitor (calphostin C and Go6976) were obtained from Calbiochem.…”
Section: Reagentsmentioning
confidence: 99%